COMPARATIVE STUDY THE EFFECT OF ISLAMIC ETHICAL IDENTITY ON PERFORMANCE OF ISLAMIC BANK - Utami, Indah Setia; Hidayati, Berlina (Universitas Negeri Yogyakarta, 2023)
The current business environment and financial performance are focus of current Islamic banking empirical research. Optimizing wealth is the main objective of the business environment of companies in all countries, including Islamic banking, where this may have eliminated the intermediation function of Islamic banks to carry out activities that are more in line with the framework of the Maqasid Syariah approach. This research aims to analyze whether there are differences in the influence of index EII on performance between sharia banking in three area with muslim majority. The research method uses content analysis of the 2016-2020 financial reports and multiple regression analysis. Samples were taken from three regions with the largest market shares, including Indonesia, Malaysia and countries in the GCC. The research results show that in Indonesia and Malaysia, EII has no effect on financial performance, while in the GCC EII has an effect on financial performance. This illustrates that there are differences between Indonesia-Malaysia and the GCC, where in Indonesia and Malaysia, customer preferences do not focus on how widely banks implement Islamic ethical identities. Meanwhile, in the GCC, customers consider the application and disclosure of Islamic ethical identity to be taken into consideration in determining a sharia bank. Key words: Ethical Identity Index, Financial Performance, Islamic Banks